Short-Term PCB (Aroclor 1254) Toxicity on Few Phosphatases in Mice Brain - Shweta Pathak; Rahul Kundu (SAGE Publishing, 2013)
The present communication reports the dose and duration dependent toxicity of a PCB, Aroclor 1254, to a few ion dependent ATPases, Acid phosphatase, Alkaline phosphatase and Glucose-6-phosphatase in the whole brain tissue of mice. Two groups of mice were subjected to two sublethal doses (0.1 and 1 mg kgbw −1 day −1 ) of PCB orally and exposed for 4, 8 or 12 days. A separate control group received the corn oil vehicle for the same exposure times. The observed results indicated exposure duration dependent changes in the enzymatic levels in the brain. The results suggest that the alteration in the enzymatic activity was possibly due to imposed oxidative stress generated by Aroclor 1254 on membrane-bound ion-dependent ATPases and other phosphatases in the brain tissue.